Hak Pengelolaan Lahan dalam Pembangunan Kawasan Investasi Pulau Rempang Ditinjau dari Hukum Positif Indonesia - Naufal Rahman, Afkaar; Tjoneng, Arman (Universitas Ekasakti, 2023)
The development of the Rempang Eco-City Investment Area is included in the National Strategic Project in 2023. In developing the investment area, the Government authorizes the Batam Free Trade and Free Port Area Concession Agency, hereinafter referred to as BP Batam, in the form of Management Rights (HPL). However, the authority is difficult to understand its legal position by various circles of society. The purpose of this study is to analyze the legal legality of land management and recognition of the existence of indigenous peoples as well as the protection of rights to communities affected by land vacancies for investment purposes on Rempang Island, Batam. The research method in this paper uses a normative juridical method with statutory approach and conceptual approach. The result of this research is that BP Batam does not have a strong basis as the holder of management rights to vacate the land currently occupied by the people of Rempang Island Batam. This is because BP Batam has not yet obtained the certificates for the management rights of Rempang Island and there is no legal basis related to the compensation budget either in the form of compensation or other programs. In addition, there is no clear recognition of the existence of indigenous peoples around Rempang Island. The efforts to protect the rights of people affected by land vacancies for investment purposes on Rempang Island Batam can be done by preventive efforts, repressive efforts and judicial efforts.